METODE PEMBELAJARAN BAHAN MAGNET DAN IDENTIFIKASI KANDUNGAN SENYAWA PASIR ALAM MENGGUNAKAN PRINSIP DASAR FISIKA - Sunaryo Sunaryo (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: A Method in Learning Magnetic Substance Characteristics and Identifying Natural Sand Compound Contents Through Basic Principles in Physics. This study was conducted by separating ferrate sand from natural sand in an area in Indramayu Regency in the form of the titanomagnetite Fe2.5Ti0.5O4 compound by means of a magnetic separator with a power of 0.3 tesla. Using this method, the titanomagnetite content of the natural sand was capable of being improved from 32% to 63.6% (for sand in River Cimanuks tributary) based on the analysis using XRD (X-Ray Difractometer) using the GSAS (General Structure Analisis System) program with a Chi2 of 1.454 and Wrp as a correction factor for the difference in the intensity of the two patterns was 0.1142 (11.42%). The value of Chi2 which was almost 1 dan and that of Wrp which was almost 10% showed that the data were acceptable (with a probability of 0.1). To enhance the titanomagnetite content of the separation product, an extraction-solving process was conducted using HCl 32% and NH4OH 25%. The results of the analysis using XRF (X-Ray Flourosence) showed that the content which was most probably a titanomagnetite compound increased its weight fraction to almost 100%. Keywords: ferrate sand, titanomagnetite, permanent magnet